THE TLR4 299GLY POLYMORPHIC ALLELE IS ASSOCIATED WITH REDUCED EFFICACY OF AZITHROMYCIN AND PIOGLITAZONE, INCLUDED IN THE COMPREHENSIVE TREATMENT OF PATIENTS WITH CORONARY HEART DISEASE - O.V. Skochko (Проблеми екології та медицини)
The Asp299Gly polymorphism of the TLR4 gene plays an important role in the pathogenesis of coronary heart disease (CHD). The purpose of the work is to conduct a comparative analysis of the clinical efficacy of azithromycin and pioglitazone against the background of complex therapy taking into account the Asp299Gly polymorphism of the TLR4 gene in patients with CHD. Materials and methods. The study included 40 people with CHD in the age group 45-68 years, divided into 2 groups of observation: the first group (n = 20) received, together with the integrated therapy, azithromycin at a dose of 500 mg/day for 3 days, then 500 mg/week for 6 months, the second group (n = 20) - together with the combined therapy pioglitazone in a dose of 15 mg once daily, in the morning for 6 months. Duration of observation 12 months. Results. Each observation group was divided into two subgroups: the Asp/Asp genotype and the combined genotype Asp/Gly +Gly/Gly. The first observation group with the Asp/Asp genotype was 14 (70%), while the combined genotype Asp/Gly +Gly/Gly was 6 (30%), the second observation group was 17 (85%) and 3 (15% ), respectively. The acceptance of azithromycin from Asp (Asp/Asp) allele carriers, led to a more effective reduction in the size of the ACS, the diameter of the stenosis and TSC, partial or complete eradication of the parodontopathogenic microflora in the oral cavity. The use of pioglitazone in carriers of the Asp allele (Asp/Asp) caused a more pronounced decrease in the diameter of the stenosis, moderate anti-inflammatory and pronounced hypoglycemic, hypolipidemic effects. Conclusions The data obtained by us showed that in patients with CHD, carriers of Asp allele, a high susceptibility to treatment was detected, and the presence of the Gly mutant allele of the TLR-4 gene was associated with a reduced therapeutic efficacy of the investigational drugs, against the background of a standard course of treatment, which indicates the pharmacogenetic peculiarity of susceptibility to the action of the investigational drugs and should be taken into account in clinical practice.